Time-resolved gain dynamics in InGaN MQWs using a Kerr gate - Taylor, R; Smith, J; Rice, J; Ryan, J; Someya, T; Arakawa, Y (2003)
The Kerr gate technique is used to time-resolve the gain in an In0.02Ga0.98N/In0.16Ga0.84N multiple quantum well sample. A new way of analyzing the data in such a variable stripe length method gain experiment is used to analyze the time-resolved spectra. The dynamics of the emission and gain are discussed. These measurements suggest that the photoexcited carriers must localize (possibly at indium-rich sites) before strong stimulated emission is seen. (C) 2002 Elsevier Science B.V. All rights reserved.